To what extent has the UK Government achieved its aim of providing certainty to businesses in relation to the National Security and Investment Act 2021? - Jai Mann (UCL Journal of Law and Jurisprudence, 2024)
Abstract: The National Security and Investment Act 2021 gave the UK Government sweeping powers to intervene in mergers and acquisitions in a broad range of scenarios. Because of this, the UK Government, when it announced plans for the Act, set out its aim to provide sufficient certainty to businesses so that the Act does not have a detrimental impact on investment in the UK. However, complaints about a lack of certainty about the Act amongst businesses and investors have persisted. This paper explores the two main concerns about the Act’s uncertainty - the lack of a ‘national security’ definition and the unclear definitions of the 17 mandatory notifiable sectors - and demonstrates that claims of a lack of certainty in these areas are largely unfounded and therefore, the Government has largely succeeded in its aim of providing certainty to businesses in relation to the Act.